Elastic response of anisotropic Gyroid cellular structures under compression: Parametric analysis - Xing Peng; Qiyuan Huang; Yali Zhang; Xiaogang Zhang; Tongtong Shen; Haoyu Shu; Zhongmin Jin (Materials & Design, 2021)
Triply periodic minimal surface (TPMS) is identified as a suitable model for designing porous structures. Gyroid cellular structure (GCS) is the most widely studied type of TPMS structure. The majority of previous studies on GCS have focused on its isotropic structure. However, as a potential candidate for bone repair, anisotropic structures need to be considered. This study presented a strategy to control the anisotropy of GCS by changing its geometrical parameters. The finite element method was subsequently applied to determine the elastic response of anisotropic GCS under compression. The degree of anisotropic (DA) of GCS was evaluated in terms of the ratio of equivalent elastic modulus in vertical and horizontal directions. Within the parameters considered, the DA of GCS varied from 0.17 to 3.6, as compared with 0.2 to 4 for human bones. The main factors affecting the anisotropic elastic response of GCS were structure anisotropy, porosity, and loading direction. The elastic modulus of the anisotropic GCS was in the range 0.03 to 5.6GPa for titanium alloy, as compared with 0.1 to 4.5GPa for human trabecular bone. Combining the porosity and anisotropic models of GCS can offer a scaffold that matches closely the human bone mechanical environment.